A novel model of autologous tooth transplantation for the study of nerve recruitment - Teresa E. Fowler; Doan T. Bloomquist; Caroline Glessner; Poonam Patel; Jeffrey N. James; Kathryn Bollinger; Lynnette P. McCluskey; Ryan F. Bloomquist (BMC, 2024)
Abstract Background Limited treatment options exist for damaged nerves and despite impressive advances in tissue engineering, scientists and clinicians have yet to fully replicate nerve development and recruitment. Innervation is a critical feature for normal organ function. While most organs are innervated prior to birth, a rare example of postnatal nerve recruitment occurs in the natural development of secondary teeth during adolescence. Many animals undergo postnatal shedding of deciduous teeth with development and eruption of secondary teeth, a process requiring recruitment of nerve and vasculature to each tooth pulp for viability. Here, the investigators created a novel model for the study of postnatal innervation by exploiting the natural phenomenon of tooth-driven nerve recruitment. Methods The investigators theorized that developing teeth possess a special capacity to induce innervation which could be harnessed in a clinical setting for nerve regeneration, and hyptothesized that a transplant model could be created to capture this phenomenon. In this descriptive study, a rat model of autologous tooth transplantation and de novo nerve recruitment was developed by surgically transferring whole developing molars to the autologous tibia. Results Downstream histological analysis performed 6 to 14 weeks after surgery demonstrated integration of molar into tibia in 81% of postoperative rats, with progressive pulpal expression of nerve marker ß-tubulin III suggestive of neuronal recruitment. Conclusions These findings provide a novel model for the study of organ transplantation and support the theory that developing dental tissues may retain nerve-inductive properties postnatally.